2018
DOI: 10.1002/cssc.201801759
|View full text |Cite
|
Sign up to set email alerts
|

Surface Functional Groups and Electrochemical Behavior in Dimethyl Sulfoxide‐Delaminated Ti3C2Tx MXene

Abstract: Functional groups in two-dimensional (2D) Ti C T MXene are an important factor influencing electrochemical performance in many applications involving energy storage, electrochemical sensors, and water purification. However, after dimethyl sulfoxide (DMSO) delamination, the effect of surface functionalities in Ti C T is still unclear and there are no systematic reports on its capacitive behavior. Experiments and theoretical calculations confirm the relationship between different surface functionalities, the DMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(55 citation statements)
references
References 31 publications
1
53
1
Order By: Relevance
“…Based on the neutron scattering measurements of Ti 3 C 2 T x , it is pointed out that interlayer interactions can be described by hydrogen bonding between O or F groups of one side of nanosheet and the ‐OH surface groups of the opposing side, and van der Waals bonding of O and/or F atoms between the sheets . The strength of interlayer hydrogen bonding depends on the orientation of the ‐OH groups relative to the layers and the amount of ‐OH relative to the ‐O and ‐F moieties positioned on the opposing surface . When water molecules are present between the layers, the hydrogen bonds form on the sheet surfaces.…”
Section: Properties Of Mxenesmentioning
confidence: 99%
“…Based on the neutron scattering measurements of Ti 3 C 2 T x , it is pointed out that interlayer interactions can be described by hydrogen bonding between O or F groups of one side of nanosheet and the ‐OH surface groups of the opposing side, and van der Waals bonding of O and/or F atoms between the sheets . The strength of interlayer hydrogen bonding depends on the orientation of the ‐OH groups relative to the layers and the amount of ‐OH relative to the ‐O and ‐F moieties positioned on the opposing surface . When water molecules are present between the layers, the hydrogen bonds form on the sheet surfaces.…”
Section: Properties Of Mxenesmentioning
confidence: 99%
“…At present, there are many methods for accelerating the exfoliation of materials, including: (1) mechanical methods: Feng et al [56] showed the ultrasonic treatment-assisted exfoliating process could inhibit the formation of a stable force between layers to obtain Ti 3 C 2 T x sheets with rich functional groups on the surface, but also cause the problem of a small lateral dimension. (2) The introduction of repulsion groups: Qian et al [61] revealed that the repulsion between the methyl group of dimethyl sulfoxide (DMSO) organic intercalant and the hydroxyl group on the surface of Ti 3 C 2 T x contributes to increase the interlayer spacing. Meanwhile, -F is replaced partly by a hydroxyl group during the exfoliating, leaving the high boiling organic reagent [62].…”
Section: Preparation Of Ti C 2 T Xmentioning
confidence: 99%
“…From the XPS Ti2p region (Fig. 2d), the binding energies of approximately 455, 456, 458 and 569 eV were assigned to Ti2p 3/2 for Ti-C bond, Ti (Ⅱ), Ti (III) and Ti (IV)-O bond respectively, and the binding energies above 460 eV presented the corresponding peaks of Ti2p 1/2 electron orbit [38][39]. Obviously, Ti (IV)-O bond was much stronger in TM-Ti 3 C 2 T x than the other two samples and was absent in HF-Ti 3 C 2 T x , which well identified the results of the Raman analysis.…”
Section: Fig 1a Schematically Illustrates the Fabrication Progress Omentioning
confidence: 99%